PENGEMBANGAN APLIKASI WEB BERBASIS FLEXBOX UNTUK PENGELOLAAN JADWAL PRODUKSI DAN DOKUMEN DIGITAL MENGGUNAKAN FRAMEWORK BULMA DI PT. GRAMEDIA - Gunadi, Goldie (ISTEK WIDURI, 2019)
PT. Gramedia is the largest printing service provider company in Indonesia. Besides in Jakarta, PT. Gramedia also opened several branches / sites in several regions, namely: Cikarang, Bandung, Surabaya, Medan, Bawen, Bali, Makassar and Palembang. The problem in this research is the process of delivering production schedule information and sending digital documents which are still carried out by production administration officers using fax machines, electronic mail (e-mail) and also messaging applications such as whatsapp. So that the production process at each site can run and well-coordinated applications are needed that can handle the production process and digital documents in PDF format that are needed as supporting information for centralized production. The application made consists of flexbox-based web applications and can be accessed by every user quickly and easily. The Bulma framework is needed so that the web application development process becomes faster and more efficient, because Bulma provides various libraries and web application components needed. The resulting web application can solve the problem of PT. Gramedia, easy to use, has a responsive display with an attractive layout and has compatibility with various mobile devices in use today.